CARDIOLOGICAL DIAGNOSTIC APPROACH TO CHILDREN WITH CONSCIOUSNESS DISORDERS - Mišanović, Verica; Viteškić , Selma; Begić, Nedim; Mulać, Ahmed; Dizdar, Selma; Anić , Duško; Terzić , Sabina; Kovačević Prstojević, Jelena; Čengić, Adisa; Begić , Zijo; Užičanin , Sajra; Međedović , Edin; et al. (Sanamed, 2025)
Introduction:Syncope is one of the most common reasons for seeking medical attention in the pediatric population. The underlying etiology ranges from benign causes to potentially life-threatening conditions.Objective:This cross-sectional retrospective study aimed to cardiologically evaluate children presenting with syncope and identify potential predictive parameters for cardiogenic syncope, the most dangerous type of syncope.Patients and Methods: Data from 100 children aged 6 to 18 years who presented with syncope were retrospectively collected from medical records at the Pediatric Clinic of the Clinical Center of the University of Sarajevo between January 1, 2021, and December 31, 2022. Binary logistic regression was used to examine the predictive significance of the studied parameters.Results: Of the 100 children with documented syncope, 71.0% were girls, with the peak incidence of syncope episodes occurring at age 15. There were no statistically significant differences in height, weight, or BMI between boys and girls. The most common cardiac diagnosis was sinus arrhythmia, while headache was the most frequent non-cardiac symptom. Seventy-three percent of patients experienced more than one syncope episode, with the highest percentage occurring at school. Prodromal symptoms were present in 87% of cases, whereas palpitations and chest pain prior to syncope were reported in 10% and 12% of cases, respectively. Among the 49 patients with abnormal ECG findings, 29% had sinus arrhythmia and 25% had incomplete right bundle branch block. The most common echocardiographic finding was mild pulmonary valve regurgitation, which is considered a normal variant. Of all studied parameters, only EEG demonstrated significant predictive value for cardiogenic syncope (p = 0.035, EXP(B) = 2.99).Conclusion:EEG findings have predictive significance for cardiogenic syncope in children. A borderline EEG increases the odds of cardiogenic syncope by approximately threefold.
Keywords: Syncope; Pediatric Population; EEG; Echocardiography; Predictive Parameters; Clinical Characteristics; Electrocardiography